2017
DOI: 10.1007/s13205-017-0908-1
|View full text |Cite
|
Sign up to set email alerts
|

Allelic variation at high-molecular weight and low-molecular weight glutenin subunit genes in Moroccan bread wheat and durum wheat cultivars

Abstract: Glutenin is a major protein fraction contributing to the functional properties of gluten and dough. The glutenin constitutes 30–40% of the protein in wheat flour and about half of that in gluten. It is essential to identify correct glutenin alleles and to improve wheat quality by selecting alleles that exert favorable effects. Moroccan wheat cultivars are unique in West Asia and North Africa region, since many of them possess resistance to Hessian fly, a pest, which is becoming important in other countries in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 45 publications
2
15
0
Order By: Relevance
“…In the presented work, a similar result was found no cultivar Ax2* among genotypes from Germany. The analysis carried out by Henkrar et al (2017) was similar to the study of Jin et al (2011). These authors identified Ax2* in 60% of Moroccan bread wheat cultivars, while Ax1 in 25% and Axnull in 15%.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…In the presented work, a similar result was found no cultivar Ax2* among genotypes from Germany. The analysis carried out by Henkrar et al (2017) was similar to the study of Jin et al (2011). These authors identified Ax2* in 60% of Moroccan bread wheat cultivars, while Ax1 in 25% and Axnull in 15%.…”
Section: Discussionsupporting
confidence: 55%
“…1 9 94°C 5 0 ; 40 9 (94°C 1 0 ; 63°C 1 0 ; 72°C 1 0 ); 1 9 72°C 10 0 conducted in many studies (Atanasova et al 2009;Brönneke et al 2000;Henkrar et al 2017;Jin et al 2011;Ma et al 2003;Moczulski and Salmanowicz 2003). The adequate composition of these proteins plays a particularly important role in conditioning the technological properties of wheat.…”
Section: Discussionmentioning
confidence: 99%
“…Glu-1 loci contains genes, which encode x-type and y-type glutenin subunits based on their molecular weight. HMW-GS play important role in determining wheat gluten and dough elasticity (Shewry et al, 2002;Henkrar et ., 2017). Dough properties and bread-making quality are influenced in negative or positive way by HMW-GS.…”
Section: Abstraktmentioning
confidence: 99%
“…On the short arm of chromosomes are Glu-A3, Glu-B3 and Glu-D3 loci, which encode LMW-GS (Henkrar et al, 2017).…”
Section: Abstraktmentioning
confidence: 99%
“…Glutenins can be further classified into two groups based on high and low molecular weight subunits (HMW-GS and LMW-GS) reflected by their mobility during sodium dodecyl sulfate polyacrylamide gel electrophoresis (SDS-PAGE). The HMW-GS comprise about 20-30% of the glutenin (Shewry et al, 1992;Henkrar et al, 2017). LMW-GS, the major class of glutenin subunits, accounts for 70-80% of the glutenin and a strong positive correlation of LMW-GS with durum wheat quality has been reported [reviewed by (Sissons, 2008)].…”
Section: Introductionmentioning
confidence: 99%